Multiple endocrine neoplasia type 1 (MEN1): analysis of 1336 mutations reported in the first decade following identification of the gene. - Lemos, M; Thakker, R (2008)
Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant disorder characterized by the occurrence of tumors of the parathyroids, pancreas, and anterior pituitary. The MEN1 gene, which was identified in 1997, consists of 10 exons that encode a 610-amino acid protein referred to as menin. Menin is predominantly a nuclear protein that has roles in transcriptional regulation, genome stability, cell division, and proliferation. Germline mutations usually result in MEN1 or occasionally in an allelic variant referred to as familial isolated hyperparathyroidism (FIHP). MEN1 tumors frequently have loss of heterozygosity (LOH) of the MEN1 locus, which is consistent with a tumor suppressor role of MEN1. Furthermore, somatic abnormalities of MEN1 have been reported in MEN1 and non-MEN1 endocrine tumors. The clinical aspects and molecular genetics of MEN1 are reviewed together with the reported 1,336 mutations. The majority (>70%) of these mutations are predicted to lead to truncated forms of menin. The mutations are scattered throughout the>9-kb genomic sequence of the MEN1 gene. Four, which consist of c.249_252delGTCT (deletion at codons 83-84), c.1546_1547insC (insertion at codon 516), c.1378C>T (Arg460Ter), and c.628_631delACAG (deletion at codons 210-211) have been reported to occur frequently in 4.5%, 2.7%, 2.6%, and 2.5% of families, respectively. However, a comparison of the clinical features in patients and their families with the same mutations reveals an absence of phenotype-genotype correlations. The majority of MEN1 mutations are likely to disrupt the interactions of menin with other proteins and thereby alter critical events in cell cycle regulation and proliferation.